HUBUNGAN ANTARA MATA KULIAH KEWIRAUSAHAAN DENGAN MINAT BERWIRAUSAHA MAHASISWA ANGKATAN 2019, PROGRAM STUDI SOSIOLOGI, FAKULTAS ILMU SOSIAL DAN ILMU POLITIK, UNIVERSITAS NUSA CENDANA - Yohana Tiu; Hildigardis M.I. Nahak; Christine E. Meka (Jurnal Pluralis, 2023)
The purposes of this study are: 1. To find out how the entrepreneurship course at Nusa Cendana University, especially in the Sociology study program, is conducted. 2. To find out the interest of sociology students in entrepreneurship. 3. To find out the relationship between entrepreneurship courses and students' interest in entrepreneurship in the Sociology study program at Nusa Cendana University. This research is a quantitative descriptive research. This study aims to explain, describe or describe existing phenomena using numbers. The theory used in this study is the neo-classical economic growth theory, in which this theory puts forward the idea that individual freedom runs fully and government interference in economic life should be kept to a minimum. The number of respondents in this study were 84 students. The results of the correlation test show that the entrepreneurship subject variable (X) has a relationship or correlation with student interest in entrepreneurship (Y). Based on the results of the correlation test, it can be concluded that the entrepreneurship course (X) has a positive effect on the interest in entrepreneurship of sociology students (Y) in the 2019 class, Faculty of Social and Political Sciences, Undana, which is indicated by a value of 0.000, this means that the significance value is 0, 05 and the person correlation is positive. If the correlation is positive, then the entrepreneurship courses in the sociology study program are optimal enough to increase students' interest in entrepreneurship. Based on the results of the research and discussion, it can be concluded that the entrepreneurship course (X) has a relationship or correlation with student interest in entrepreneurship (Y). This interest in entrepreneurship is needed so that students are able to compete in the world of work after graduating from university. Therefore the role of entrepreneurship courses is very important in fostering interest and forming entrepreneurial character from students to face the challenges of the world of work.